Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 12445 species occurrences available in GBIF matching the query: { "DatasetKey" : [ "is Museo Nacional de Ciencias Naturales, Madrid. Colección de Tejidos y ADN" ] } The dataset includes 12445 records from 1 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000142-150304104939900/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences